Analisis Perhitungan Beban Pendinginan pada Gedung Advanced Research Laboratory Fakultas Teknik Universitas Udayana dengan Metode Cooling Load Temperature Difference - Sandi, Arles Kurnia; Wijaksana, Hendra; Suarnadwipa, I Nengah (Teknik Desain Mekanika, 2024)
Abstractt Air conditioning in lecture buildings aims to create comfortable conditions for occupants in a room through the process of treating air in regulating temperature, cleanliness, humidity and distribution simultaneously. Calculation of the cooling load aims to make the capacity at peak load as desired, reduce damage due to unit work that is too heavy and reduce energy wastage. At the time of writing in this study, the authors used the cooling load temperature difference method in calculating the cooling load. The calculation of this method is based on determining the position of the building, dimensions, details of building materials, determining the air temperature inside and outside the building and calculating internal and external loads. From the results of calculating the cooling load in the Advanced Research Laboratory building, Faculty of Engineering, Udayana University, the author can recommend the capacity of Split AC & Central AC. The total value of the cooling load for the entire building with a safety factor of 10% is 1,930,101.204 btu/h or 565.66 kW. Keywords: Cooling load, CLTD, Safety factor.